The View from Inside the System: How Police Explain Their Response to Sexual Assault. Issue 3 (18th October 2016) - Shaw, Jessica; Campbell, Rebecca; Cain, Debi
Abstract: Prior research has documented the problematic community response to sexual assault: the majority of sexual assaults reported to police are never prosecuted. Social dominance theory suggests that this response is a form of institutional discrimination, intended to maintain existing social structures, and that police personnel likely draw upon shared ideologies to justify their decision‐making in sexual assault case investigations. This study drew upon social dominance theory to examine how police justified their investigatory decisions to identify potential leverage points for change. The study revealed that the likelihood of a case referral to the prosecutor increased with each additional investigative step completed; of the different types of justifications provided by police for a less‐than‐thorough investigative response and stalled case, blaming the victim for the poor police investigation proved to be the most damaging to case progression; and the type of explanation provided by police was impacted by specific case variables. As suggested by social dominance theory, the study demonstrates that police rely on several different mechanisms to justify their response to sexual assault; implementing criminal justice system policies that target and interrupt these mechanisms has the potential to improve this response, regardless of specific case factors.